Knowledge, Attitude and Perceptions towards COVID-19 Vaccination among South Indian (Telangana) Population - A Cross Sectional Study - Barigela, Srimanth Kumar; Galimudi, Rajesh Kumar; Kadarla, Shivani; Rani, Durga Neeharika; Reddy, Pardha P.; Jangala, Madhavi; Kumar, Sunita G (Archives of Clinical and Medical Case Reports, 2022)
Objective: The Covid-19 pandemic caused unprecedented damage to human health all over the globe. Knowledge, Attitudes and Perceptions (KAP) are backbone to constrain Covid-19. The present study investigated the KAP in the general Telangana (South Indian) population. Study Design: A cross sectional study was conducted on 734 people using specific questionnaire by google forms to generate data on knowledge, attitudes and perceptions among socio-demographic characteristics in the general population for a period of 30 days from 23rd May, 2021 to 21st June, 2021. Methods: Descriptive statistics, t-test, one way analysis of variance (ANOVA), chi-square test, multiple logistic regression analyses were performed to analyse the results. Results: The results on knowledge showed that 96.73%, 45.64% and 88.42%, of participants (?2 values of 1.815, 2.044 and 3.742) know about Covid-19 vaccines, its side effects and the efficacy of Indian vaccine, etc. 66.08% and 88.28% of the participants (?2 Values of 7.616 and 14.00) expressed that Covid-19 vaccine is safe and they would motivate their family members and friends to take vaccine. About 60% of the participants (?2 Value of 2.715) felt that it is possible to control Covid-19 even without vaccine. 71.66% of participants (?2 Value of 21.74) said that they recommend vaccination to all irrespective of age and comorbidities. 69.35% of the participants (?2 Value of 6.638) felt that people are reluctant to take vaccines, 68.53% (?2 Value of 0.4359) of them are thinking that they are not following Covid norms. The results have also indicated that certain percentage of people are not aware of following Covid norms and taking up of Covid vaccines. Conclusion: Our findings highlight